Forty thieves [large type] - Perry, Thomas, 1947- (Thorndike Press large print core series., 2016)
"Sid and Ronnie Abel are a first-rate husband-and-wife detective team, both retirees of the LAPD. Ed and Nicole Hoyt are married assassins-for-hire living in the San Fernando Valley. Except for deadly aim with a handgun, the two couples have little in common--until they are both hired to do damage control on the same murder case. As the book races toward a high-octane climax, the Abels must fend for their own lives as they circle ever closer to the truth" --